Protective effects of galacturonic acid-rich vinegar brewed from Japanese pear in a dextran sodium sulfate-induced acute colitis model - Takashi Wakuda; Kazuo Azuma; Hiroyuki Saimoto; Shinsuke Ifuku; Minoru Morimoto; Ichiro Arifuku; Masahito Asaka; Takeshi Tsuka; Tomohiro Imagawa; Yoshiharu Okamoto; Tomohiro Osaki; Saburo Minami (Journal of Functional Foods, 2013)
The effects of pear vinegar (PV), which was specially brewed for enhanced galacturonic acid content, on the DSS-induced ulcerative colitis (UC) mouse model were evaluated. PV improved clinical symptoms, colon inflammation, and histological tissue injury in the DSS-induced acute UC mouse model. Moreover, PV suppressed inflammation due to acute UC by suppressing the myeloperoxidase (MPO)-mediated activation of inflammatory cells such as leukocytes and decreasing the serum concentration of IL-6. Our results demonstrated the protective action of PV in the DSS-induced acute UC mouse model. On the other hand, commercial apple vinegar did not show a protective effect in the DSS-induced acute UC mouse model. Our findings indicate that PV may act as a new functional food for inflammatory bowel disease patients.